The Role of NADPH Oxidase in Neuronal Death and Neurogenesis after Acute Neurological Disorders - Song Hee Lee; Minwoo Lee; Dong Gyun Ko; Bo Young Choi; Sang Won Suh (MDPI AG, 2021)
Oxidative stress is a well-known common pathological process involved in mediating acute neurological injuries, such as stroke, traumatic brain injury, epilepsy, and hypoglycemia-related neuronal injury. However, effective therapeutic measures aimed at scavenging free reactive oxygen species have shown little success in clinical trials. Recent studies have revealed that NADPH oxidase, a membrane-bound enzyme complex that catalyzes the production of a superoxide free radical, is one of the major sources of cellular reactive oxygen species in acute neurological disorders. Furthermore, several studies, including our previous ones, have shown that the inhibition of NADPH oxidase can reduce subsequent neuronal injury in neurological disease. Moreover, maintaining appropriate levels of NADPH oxidase has also been shown to be associated with proper neurogenesis after neuronal injury. This review aims to present a comprehensive overview of the role of NADPH oxidase in neuronal death and neurogenesis in multiple acute neurological disorders and to explore potential pharmacological strategies targeting the NADPH-related oxidative stress pathways.